2018
DOI: 10.1542/peds.2018-1938
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes of Very Preterm or Very Low Birth Weight Triplets

Abstract: OBJECTIVES:To compare the neonatal outcomes of very preterm triplets with those of matched singletons using a large international cohort. METHODS:A retrospective matched-cohort study of preterm triplets and singletons born between 2007 and 2013 in the International Network for Evaluation of Outcomes in neonates database countries and matched by gestational age, sex, and country of birth was conducted. The primary outcome was a composite of mortality or severe neonatal morbidity (severe neurologic injury, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
5
24
3
Order By: Relevance
“…The iNeo database contains information on >200,000 VPT infants, a population size that has allowed us to evaluate the association between exposure to risk factors and neonatal outcomes with a very high precision and especially study rare exposures such as severe congenital heart defects (34). For example, we identified that maternal diabetes was not associated with composite adverse outcome of mortality or major morbidities in VPT neonates (35), and that triplets of <29 weeks' GA had similar outcomes to singletons of <29 weeks' GA (36). In contrast, preterm neonates of <29 weeks GA born to mothers with hypertensive disorder were associated with lower odds of mortality, severe brain injury and treated ROP and higher odds of BPD than preterm neonates of <29 weeks GA born to normotensive mothers (37).…”
Section: Aim 1: Compare National Neonatal Outcomes and Health Servicementioning
confidence: 94%
“…The iNeo database contains information on >200,000 VPT infants, a population size that has allowed us to evaluate the association between exposure to risk factors and neonatal outcomes with a very high precision and especially study rare exposures such as severe congenital heart defects (34). For example, we identified that maternal diabetes was not associated with composite adverse outcome of mortality or major morbidities in VPT neonates (35), and that triplets of <29 weeks' GA had similar outcomes to singletons of <29 weeks' GA (36). In contrast, preterm neonates of <29 weeks GA born to mothers with hypertensive disorder were associated with lower odds of mortality, severe brain injury and treated ROP and higher odds of BPD than preterm neonates of <29 weeks GA born to normotensive mothers (37).…”
Section: Aim 1: Compare National Neonatal Outcomes and Health Servicementioning
confidence: 94%
“…Causal factors linked to PTB include medical conditions [ 20 ], genetic influences [ 21 , 22 , 23 ], environmental exposure [ 24 , 25 ], infertility treatments [ 26 , 27 ], as well as behavioral and socioeconomic factors [ 28 , 29 , 30 ]. While extreme to very PTBs have been extensively studied, and the associated morbidities are well-documented [ 31 , 32 , 33 ], studies on infants born at later stages of pregnancy, particularly late PTBs and ETBs, are lacking. Thus, in this population-based study, we aimed to assess the incidence of PTB and ETB over a period of 12 months in Qatar, and examine the associated neonatal and maternal risk factors, as well as the feto-maternal consequences in the perinatal-neonatal period.…”
Section: Introductionmentioning
confidence: 99%
“…Technological innovations make it possible to combine different information sources and provide information on a more detailed level. Clinically collected data from EHR with well-regulated, international, and privacy proof unrestricted access for researchers, such as the MIMIC-III and AmsterdamUMCdb database, and the increased availability of raw trial data could bring about a revolution in research on preterm neonates (149)(150)(151)(152).…”
Section: Large Databasesmentioning
confidence: 99%